Chris Johnson's Writing Lesson. Issue 1 (March 2020) - Kamuf, Peggy
Abstract : This essay traces the insistent and repeated attention Christopher Johnson pays to the episode in Tristes tropiques that Lévi-Strauss calls 'The Writing Lesson' and that Derrida reads as a parable and symptom of the ethnophonocentrism dictating the anthropologist's account. Johnson returns to this scene and this reading in each of his three books, and at some length in two of them. There is also an appreciative assessment of the writing lesson Johnson illustrates with his own work.